Next steps to improve disparities in lung cancer treatment clinical trial enrollment - Zullig, Leah L.; Carpenter, William R.; Williams, Christina D. (Annals of Translational Medicine; Vol 5, No 5 (March 15, 2017): Annals of Translational Medicine, 2017)
Cancer treatment clinical trials provide access to cutting-edge treatments. Treatment trial results are often used to guide clinical recommendations, decision-making, policies, and further intervention development to treat cancer patients in both academic centers and the community. In the USA, adults enroll in cancer treatment trials at very low rates and participants do not represent the USA cancer population (1). Because their primary objective is to assess efficacy, oncology clinical trials have stringent enrollment criteria. Compared to the general population of adults with cancer, patients that enroll in cancer treatment trials are disproportionately younger, male, physically fit, and are less likely to be from minority racial and ethnic groups (2,3). Assuring representative population heterogeneity in clinical trials is critical to assessing treatment safety and efficacy across diverse patients and assuring subsequent effectiveness among all members of the broader population. With the current trend toward personalized medicine, emerging treatments are often tailored for specific genotypes making enrollment of racially diverse groups particularly salient (4). As lung cancer is the leading cause of USA cancer deaths, lung cancer treatment trials stand to make a huge contribution in improving population cancer mortality.